Pengaruh Kredibilitas dan Literasi Zakat Terhadap Keputusan Menunaikan Zakat dengan Religiusitas Sebagai Variabel Moderating pada BAZNAS Kabupaten Temanggung - Hafiddianti, Afinda; Waluyo, Agus (Al Rikaz: Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the effect of credibility and zakat literacy on the decision of Civil Servants (ASN) to pay zakat, with religiosity as a moderating variable at BAZNAS Temanggung Regency. Data were collected through questionnaires distributed to ASN who paid zakat at BAZNAS Temanggung Regency. The sample consisted of 100 respondents selected using a non-probability sampling technique. The data obtained were processed using SPSS version 25. The t-test results show that credibility has a positive but insignificant effect on the decision to pay zakat, while zakat literacy has a positive and significant effect on the decision to pay zakat. Based on the MRA test, religiosity is able to moderate the relationship between credibility, zakat literacy, and the decision of ASN to pay zakat at BAZNAS Temanggung Regency.